IMPACT OF COVID-19 ON THE INCIDENCE OF NEWLY DIAGNOSED TYPE 1 DIABETES MELLITUS: A SINGLE-CENTRE EXPERIENCE - Zaini, Amira Yasmin Mohamed; Ridzuan, Syarifah Nursyazana Syed; Lordudass, Alexis Anandas; Zaini, Azriyanti Anuar; Samingan, Nurshadia (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Recent studies suggest the increasing occurrence of newly diagnosed type 1 diabetes mellitus during the COVID-19 pandemic. It is postulated that the COVID-19 virus triggers a cascade of autoimmune reactions leading to the development of antibodies against beta cells of the pancreas. This study investigates the incidence of newly diagnosed T1DM in a Malaysian tertiary centre during the COVID-19 era in comparison to the same duration prior to it. METHODOLOGY This is a single-centre retrospective cross-sectional study among newly diagnosed T1DM patients. Patients aged between one year to less than 18 years old, who were referred to the Paediatric Endocrine Unit of the University Malaya Medical Centre from September 2017 to August 2022 were included in this study. Data including age, gender, anthropometric measurements, diabetic ketoacidosis occurrence, biochemical results and COVID-19 status for the past three months were obtained. RESULTS Fifty-seven patients who fulfilled the criteria of T1DM were included. Thirty-two patients (56%) were diagnosed during the COVID-19 era. Forty-four patients (77%) presented with DKA. There is no difference in the incidence of DKA and the severity status between these two periods, (77% versus 76.7%, p=0.902; and 51.9% versus 53.3%, p=0.546, respectively. Although not statistically significant, more patients needed pediatric ICU admission (13 versus 9),with lower pH at presentation during the COVID-19 era (7.05 versus 7.12). More than a third (37.5%) needed intubation (p=0.019). Recovery was also longer (48 hours versus 36 hours). CONCLUSION Despite the absence of a significant statistical difference, more patients presented with more severe DKA with longer recovery during the COVID-19 pandemic. A larger multi-centre study is needed to evaluate the magnitude of the impact of COVID-19